2011
DOI: 10.1111/j.1600-0838.2009.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical self‐perception and motor performance in normal‐weight, overweight and obese children

Abstract: The aim of this study was to examine the relationships among physical self-perception, body image and motor performance in Italian middle school students. Two hundred and sixty children were categorized into normal-weight (n=103), overweight (n=86) or obese (n=71) groups. Perceived coordination, body fat and sports competence were assessed using the Physical Self-Description Questionnaire, while body image was measured using Collins' Child Figure Drawings. Individuals' perceptions of strength, speed and agilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 32 publications
(61 reference statements)
7
59
0
8
Order By: Relevance
“…33 In this context, the multidimensional nature of fitness cannot be emphasized enough and an opportunity to give overweight children fitness-related positive feedback is potentially missed if only CRF and weight-bearing tests of muscular fitness are administered. Overweight children tend to outperform normal weight children in nonweight bearing tests of strength and power, such as hand grip strength 49 (Figure 1, Panel B), medicine ball throw 50 or in weight bearing strength and power tests when performance is expressed with relative values (Figure 1, Panel C).…”
Section: The Importance Of Muscular Fitness Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 In this context, the multidimensional nature of fitness cannot be emphasized enough and an opportunity to give overweight children fitness-related positive feedback is potentially missed if only CRF and weight-bearing tests of muscular fitness are administered. Overweight children tend to outperform normal weight children in nonweight bearing tests of strength and power, such as hand grip strength 49 (Figure 1, Panel B), medicine ball throw 50 or in weight bearing strength and power tests when performance is expressed with relative values (Figure 1, Panel C).…”
Section: The Importance Of Muscular Fitness Testsmentioning
confidence: 99%
“…Indeed, muscular strength is one of the only subcomponents of physical self-concept scales on which overweight children rate themselves highly. 50 Highlighting these pupils' capabilities in this specific aspect of fitness through testing could be a way to positively reinforce a specific "athletic identity." This construct predicts sports participation and PA levels independently of gender, body mass, ethnicity, 51 and perceived task competence.…”
Section: The Importance Of Muscular Fitness Testsmentioning
confidence: 99%
“…These can be considering worrying results as physical self-perception has already been identified as an important correlate of physical activity, motor competence and performance in childhood (Raudsepp et al, 2002;Southall et al, 2004). Furthermore, previous studies have showed that in addition to lower perceptions of their physical ability, overweight children and adolescents had significantly lower actual physical competences than their normal weight peers (Morano et al, 2011;Southall et al, 2004), and children with low actual and perceived physical ability could be lead into a negative spiral of disengagement in physical activity, resulting in lower physical activity levels (Stodden et al, 2008). In fact, the less an individual engages in physical activity, the more his physical competence decreases causing the reduction of its self-perceptions.…”
Section: Discussionmentioning
confidence: 95%
“…En ellos se ha observado la asociación significativa con el concepto físico general, así como otras dimensiones específicas como condición física, fuerza o habilidad física, también sobre población adolescente (Crocker et al, 2006;Greenleaf et al, 2010;Lubans y Cliff, 2011;Morano, Colella, Robazza, Bortoli y Capranica, 2011). Además, estos autores ponen de relieve que los factores relacionados con la condición física son medidas más fiables para valorar aspectos del autoconcepto que la mera práctica de actividad física, lo que debe ser tenido en cuenta a la hora de diseñar programas de intervención que busquen mejorar el nivel de estas percepciones en poblaciones de estas edades.…”
Section: Discussionunclassified